EFEKTIVITAS SISTEM PENGOLAHAN INSTALASI PENGOLAHAN AIR LIMBAH SUWUNG DENPASAR TERHADAP KADAR BOD, COD, DAN AMONIA - Sulihingtyas, Wahyu Dwijani; Budiarsa Suyasa, I W.; Indra Wahyuni, Ni M. (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010, 2012)
The effectivity of waste water treatment systems in Suwung Waste Water Treatmant Installation Denpasar, was investigated, by analyzing its effluent Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and ammonia contents. The aims of the research are to determine the effectivity of each stage of waste water treatment and the optimum detention time of waste water in aerated lagoon and sedimentation pond, in order to reduce the BOD, COD and ammonia concentration. The results showed that the effectivity of treatment systems of waste water in Suwung Denpasar was low. The percentages of the reduction of BOD5, COD and ammonia in content stage I were 14.29, 15.66, and 33.74% respectively. More over, the reduction percentages in stage II were 20.83, 14.43, and 17.39% respectively. On the other hand, the reduction percentages from the initial to final stages were 32.14% for BOD5, 27.83% for COD and 45.26% for ammonia. The optimum detention time of waste water in aerated lagoon and sedimentation pond for reducing parameters was 5 day and 40 hour respectivel
Keywords: effectivity, treatment systems, waste water, detention time